Inhibition of lysyl oxidase‐like 2 overcomes adhesion‐dependent drug resistance in the collagen‐enriched liver cancer microenvironment. Issue 11 (27th July 2022) - Gong, Lanqi; Zhang, Yu; Yang, Yuma; Yan, Qian; Ren, Jifeng; Luo, Jie; Tiu, Yuen Chak; Fang, Xiaona; Liu, Beilei; Lam, Raymond Hiu Wai; Lam, Ka‐On; Lee, Anne Wing‐Mui; et al.
Abstract: The tumor microenvironment (TME) is considered to be one of the vital mediators of tumor progression. Extracellular matrix (ECM), infiltrating immune cells, and stromal cells collectively constitute the complex ecosystem with varied biochemical and biophysical properties. The development of liver cancer is strongly tied with fibrosis and cirrhosis that alters the microenvironmental landscape, especially ECM composition. Enhanced deposition and cross‐linking of type I collagen are frequently detected in patients with liver cancer and have been shown to facilitate tumor growth and metastasis by epithelial‐to‐mesenchymal transition. However, information on the effect of collagen enrichment on drug resistance is lacking. Thus, the present study has comprehensively illustrated phenotypical and mechanistic changes in an in vitro mimicry of collagen‐enriched TME and revealed that collagen enrichment could induce 5‐fluorouracil (5FU) and sorafenib resistance in liver cancer cells through hypoxia‐induced up‐regulation of lysyl oxidase‐like 2 ( LOXL2 ). LOXL2, an enzyme that facilitates collagen cross‐linking, enhances cell adhesion‐mediated drug resistance by activating the integrin alpha 5 (ITGA5)/focal adhesion kinase (FAK)/phosphoinositide 3‐kinase (PI3K)/rho‐associated kinase 1 (ROCK1) signaling axis. Conclusion: We demonstrated that inhibition of LOXL2 in a collagen‐enriched microenvironment synergistically promotes the efficacy of sorafenib and 5FU through deterioration of focal adhesion signaling. These findings have clinical implications for developing LOXL2‐targeted strategies in patients with chemoresistant liver cancer and especially for those patients with advanced fibrosis and cirrhosis. Abstract : In this study, we revealed the collagen‐mediated chemoresistance via activation of HIF1A/LOXL2/ITGA5/FAK/PI3K/ROCK1 signaling and showed that LOXL2 is a promising therapeutic target to enhance the efficacy of 5FU and sorafenib in resistant liver cancer patients, especially those with advanced fibrosis and cirrhosis.image